Ukraine : the social sectors during transition. - World Bank. (Washington, D.C. : World Bank, 1993)
This report lays out a strategy for Ukraine to make the transition to a market economy in the social sectors, taking into account the widespread system of benefits and the high spending on education and health inherited from the former Soviet Union.
Includes bibliographical references.
oif 09/08/16
Loan
Keywords: Economic conditions; Social conditions; Social security; Ukraine; Ukraine